2017
DOI: 10.3390/geosciences7020028
|View full text |Cite
|
Sign up to set email alerts
|

Role of Faults in Hydrocarbon Leakage in the Hammerfest Basin, SW Barents Sea: Insights from Seismic Data and Numerical Modelling

Abstract: Hydrocarbon prospectivity in the Greater Barents Sea remains enigmatic as gas discoveries have dominated over oil in the past three decades. Numerous hydrocarbon-related fluid flow anomalies in the area indicate leakage and redistribution of petroleum in the subsurface. Many questions remain unanswered regarding the geological driving factors for leakage from the reservoirs and the response of deep petroleum reservoirs to the Cenozoic exhumation and the Pliocene-Pleistocene glaciations. Based on 2D and 3D seis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 75 publications
1
34
1
Order By: Relevance
“…Seafloor features related to fluid expulsion processes e.g. pockmarks and craters are widespread and their formation, in some cases, is related to the destabilization of methane hydrates 19 , 30 fed from leaking Mesozoic hydrocarbon reservoirs 31 34 . In addition, the Barents Sea is a paleo-analogue of the Antarctic 35 , and therefore may help better predict the evolution of the modern gas hydrate systems beneath the marine-based West Antarctic Ice Sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Seafloor features related to fluid expulsion processes e.g. pockmarks and craters are widespread and their formation, in some cases, is related to the destabilization of methane hydrates 19 , 30 fed from leaking Mesozoic hydrocarbon reservoirs 31 34 . In addition, the Barents Sea is a paleo-analogue of the Antarctic 35 , and therefore may help better predict the evolution of the modern gas hydrate systems beneath the marine-based West Antarctic Ice Sheet.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of data on subsea permafrost in the Arctic shelf collected through Russian and international research projects [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] has revealed large-scale methane emission from bottom sediments into water and on into the atmosphere. The gases in the Arctic shelf are often attributed to increasing microbial methane generation, migration of gas through taliks and faults, as well as to decomposition of intrapermafrost and subpermafrost gas hydrates during progressive degradation of subsea permafrost [11,[16][17][18][19][20][21]. The dissociation of hydrates related to subsea permafrost degradation has been largely discussed lately as the main mechanism maintaining the emanation of methane [4,14,18,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…This helps improve both safety and the chance of success of future scientific drilling. Improved 3D seismic acquisition and processing workflows have led to significant improvements in 3D resolution and a reduced reliance on dedicated site surveys (Games and Self, 2017;Oukili et al, 2019). Comparison of the 3D seismic volumes as pseudo site surveys within Proposal 909, against the recently acquired 2D UHR site survey lines, shows that the quality and resolution of imaging are mostly consistent across the two data types, confirming its suitability (comparison in Figs.…”
Section: Benefits To Future Projectsmentioning
confidence: 75%
“…Today, the acquisition of large-scale 3D seismic reflection datasets in frontier basins provides spatial coverage that far exceeds most conventional site surveys (Games and Self, 2017). The processing of these datasets has improved sufficiently to provide a vertical resolution that approaches that of a traditional site survey and often provides a horizontal resolution exceeding that of even closely spaced 2D seismic site surveys (Games and Self, 2017;Oukili et al, 2019). Three-dimensional seismic surveys thus minimize the need for additional data, except for particularly complicated areas (Hill, 1996;Selvage et al, 2012;Sharp and Badalini, 2013;Williams and Andresen, 1996;Roberts et al, 1996).…”
Section: Introductionmentioning
confidence: 99%